Using computational tools in collaborative environments as a basis for the development of a Ubiquitous Model of Computer Assisted Learning - Mendoza Ceballos, Jair; Chito Jiménez, Aura Marcela; Larrahondo Caicedo, Claudia Lorena (I+ T+ C- Research, Technology and Science, 2014)
The article is the result of a research project, it analyzes how students are heavy users of different technological resources available on the market for managing information: cell, “tables” and computers. Through these students access to various information systems, but especially the “social networks”. These resources will become an invaluable educational tool that teachers are not adequately leveraging to improve their teaching and learning.